Faricimab for the Treatment of Diabetic Macular Edema and Neovascular Age-Related Macular Degeneration - Lorenzo Ferro Desideri; Carlo Enrico Traverso; Massimo Nicolò; Marion R. Munk (MDPI AG, 2023)
Nowadays; intravitreal anti-vascular endothelial growth factor (VEGF) drugs are considered the first-line therapeutic strategy for treating macular exudative diseases; including wet age-related macular degeneration (w-AMD) and diabetic macular edema (DME). Despite the important clinical achievements obtained by anti-VEGF drugs in the management of w-AMD and DME; some limits still remain; including high treatment burden; the presence of unsatisfactory results in a certain percentage of patients and long-term visual acuity decline due to complications such as macular atrophy and fibrosis. Targeting the angiopoietin/Tie (Ang/Tie) pathway beyond the VEGF pathway may be a possible therapeutic strategy; which may has the potential to solve some of the previous mentioned challenges. Faricimab is a new; bispecific antibody targeting both VEGF-A and the Ang-Tie/pathway. It was approved by FDA and; more recently; by EMA for treating w-AMD and DME. Results from phase III trials TENAYA and LUCERNE (w-AMD) and RHINE and YOSEMITE (DME) have shown the potential of faricimab to maintain clinical efficacy with more prolonged treatment regimens compared to aflibercept (12 or 16 weeks) with a a good safety profile.